Fiscal measures to Reduce CO2 emissions from new passenger cars - Jordal-Jørgensen, Jørgen; Jespersen, Malene Sand (Proceedings from the Annual Transport Conference at Aalborg University, 2002)
The fuel efficiency of passenger cars is often emphasised as one of the most significant areas of action in terms of limiting the transport sector’s CO2 emission levels. This could be achieved either on the supply side through the technological development of cars, or through demand-side measures such as influencing first time buyers’ choice of car. The aim of this article is to present a model for analysis of the demand side, more specifically the relation between the CO2 emissions from new cars and the car taxation related to new car purchases in EU. The purpose of the model is twofold. Firstly, it should be used to analyse the CO2 efficiency of the car taxation in each member state. Secondly, results from model calculations should be used to illustrate what are the possibilities for the individual member states to reduce their CO2 emissions from new cars. The major conclusions from the study are: It is essential to apply a tax scheme, which is directly or indirectly CO2 related in order to provide for significant reductions in the average CO2 emissions from new cars. It is essential to differentiate the taxes in such a way that taxes for very energy effective cars are significantly lower than taxes for cars with poor energy efficiency. Fuel tax increases provide only very small reductions of the average CO2 emissions of new cars compared to vehicle taxes. The model is based on a revised and enhanced version of the Danish Car Choice model from 1997 combined with car characteristics, socio-economic data and car taxation data from the EU member states.